Junctional kyphosis after the treatment of adolescent idiopathic scoliosis - Mohsen Karami; Arash Maleki; Keyvan Mazda; Alireza Mirshemirani (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Introduction: In this retrospective study radiographic review was undertaken in patients treated for AIS (Adolescent Idiopathic Scoliosis), in order to determine the most important preoperative factors that are seen with postoperative junctional kyphosis. Material &Methods: Sagittal spine profiles were measured on the standing radiographs before surgery, after surgery and in the last follow-up postoperative visit of the patients with AIS. The following parameters were measured on lateral views: lumbar lordosis, thoracic kyphosis, the sagittal offset distance of C7 to a vertical line from postero-superior edge of S1 (Sagittal Vertical Axis-SVA) and T9 sagittal offset angle.  Results: One hundred and twenty patients with a mean 42 months of follow-up (24-112 months) were included in the study. Mean values of the parameters before corrective surgery were: lumbar lordosis 45° ± 13.6°, thoracic kyphosis 28°±18.4°, SVA 35 ± 27.2 mm and T9 offset angle, 7.8°± 5.1°. Mean values at last follow-up were: lumbar lordosis 49± 9.8°, thoracic kyphosis 35 ± 16.4°, SVA 39 ± 24 mm and T9 offset angle, 8.6°±5.8°. There were 10 upper junctional kyphosis (8.4%). T test statistics revealed significant correction of lumbar lordosis and thoracic kyphosis after fusion in all patients (P<0.001, P=0.006 respectively). Preoperative mean of T9 sagittal offset angle was higher in the patients with proximal junctional kyphosis (P=0.006). Conclusion: Normal sagittal balance of spine is essential for the optimum function of the intervertebral disks and preventing sagittal postoperative complication like proximal junctional kyphosis. More attention to preoperative sagittal parameters of the spine like T9 offset may be important to prevent such complications.